Determination of Aortic Characteristic Impedance and Total Arterial Compliance From Regional Pulse Wave Velocities Using Machine Learning: An in-silico Study - Bikia, Vasiliki; Rovas, Georgios; Pagoulatou, Stamatia; Stergiopulos, Nikolaos (Frontiers in Bioengineering and Biotechnology, 2021)
In-vivo assessment of aortic characteristic impedance (Zao) and total arterial compliance (CT) has been hampered by the need for either invasive or inconvenient and expensive methods to access simultaneous recordings of aortic pressure and flow, wall thickness, and cross-sectional area. In contrast, regional pulse wave velocity (PWV) measurements are noninvasive and clinically available. In this study, we present a noninvasive method for estimating Zao and CT using cuff pressure, carotid-femoral PWV (cfPWV), and carotid-radial PWV (crPWV). Regression analysis is employed for both Zao and CT. The regressors are trained and tested using a pool of virtual subjects (n=3818) generated from a previously validated in-silico model. Predictions achieved an accuracy of 7.40 %, r=0.90, and 6.26 %, r=0.95, for Zao, and CT, respectively. The proposed approach constitutes a step forward to noninvasive screening of elastic vascular properties in humans by exploiting easily obtained measurements. This study could introduce a valuable tool for assessing arterial stiffness reducing the cost and the complexity of the required measuring techniques. Further clinical studies are required to validate the method in-vivo.